2018
DOI: 10.1002/ejoc.201800046
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Functional‐Group‐Tolerant Synthesis of Substituted Furans through the Pd‐Catalyzed 5‐exodig Cyclization/Coupling of γ‐Acetylenic β‐Keto Esters with (Hetero)Aryl Bromides

Abstract: We report an efficient protocol for the synthesis of 2,3,5‐trisubstituted furans through the reaction of readily available γ‐acetylenic β‐keto esters with aryl and heteroaryl bromides. The reaction, which involves a 5‐exo‐dig cyclization, coupling, and isomerization of a double bond, proceeds smoothly with very low catalyst loading (0.1 mol‐%), and shows excellent functional‐group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Importantly, a similar mechanism was previously proposed by Arcadi and us for a related transformation of terminal alkynes with aryl halides, however, involvement of dihydrofuran was not experimentally proven, let alone isolated. [7,8] Moreover, an alternative cyclization mode involving syn-oxopalladation of the alkyne moiety could possibly operate and needs to be either confirmed or ruled out. Such a mechanistic scenario was proven to be involved in a related Pdcatalyzed cyclization/allylation with allyl carbonates employed as an electrophilic partner.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, a similar mechanism was previously proposed by Arcadi and us for a related transformation of terminal alkynes with aryl halides, however, involvement of dihydrofuran was not experimentally proven, let alone isolated. [7,8] Moreover, an alternative cyclization mode involving syn-oxopalladation of the alkyne moiety could possibly operate and needs to be either confirmed or ruled out. Such a mechanistic scenario was proven to be involved in a related Pdcatalyzed cyclization/allylation with allyl carbonates employed as an electrophilic partner.…”
Section: Resultsmentioning
confidence: 99%
“…Two decades ago, Arcadi showed that 2,3,5‐trisubstituted furans could be accessed directly from acetylenic β‐ketoesters and aryl iodides or triflates via a Pd‐catalyzed tandem process encompassing 5‐exo‐dig cyclization, coupling and isomerization (Scheme 1). [7] Recently we developed a protocol applicable for cheaper and more readily available, but considerably less reactive, aryl bromides featuring exceptional functional group tolerance [8] . However, several issues are still to be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[42] Chaładaj and co-workers reported an efficient Pd-catalyzed protocol for the synthesis of 2,3,5-trisubstituted furans 95 through the cyclization of 4-acetylenic ketones 93 with aryl and heteroaryl bromides 94 (Scheme 20). [43] The reaction proceeded under mild conditions with a low catalyst loading (0.1 mol%) and an excellent functional-group tolerance.…”
Section: Palladium-catalyzed Cyclizations Of 4-acetylenic Ketonesmentioning
confidence: 99%
“… 11 On the other hand, propargyl-β-ketoesters underwent 5- exo-dig oxocyclization/coupling, leading to the formation of substituted furan systems due to ambident nature of enolates of β-ketoesters. 12 Interestingly, the analogous transformation involving homopropargyl-β-ketoesters possessing an internal or terminal alkyne motif clearly led to either cyclopentenes 9 or dihydropyranes, 13 respectively.…”
Section: Introductionmentioning
confidence: 99%